Diversity of Soil Microfungi in Pine Forest at Duhok Governorate, Kurdistan Region, Iraq - Samir, Samir Kh.; Nashat, Lava H. (Science Journal of University of Zakho, 2014)
The soil microfungi inhabiting pine (Pinus brutia Tern.) forests in Atrush and Zawita, Duhok governorate(Kurdistan region),Iraq were examined by using five isolation methods with the objective to compare the diversity of soil microfungi at O1 and O2 soil horizon layers from both sites. A total of 26 genera and 51 species of soil fungi as well as yeasts and non- sporulating mycelia were isolated from the two sites. Aspergillus was represented by 17 species and thus showed the widest diversity among all recovered genera. A.niger and A.fumigatus were the most frequent species among the genus. Black aspergilli were the most common species among the genus. They were represented by five species viz A.awamori, A.foetidus, A niger, A. sclerotioniger and A.vadianes. Penicillium was the second in the number of species isolated and was represented by 6 species. These include P. cammeberti, P. citrinum, P. coryophilum, P. digitatum , p. glabrum and P. roquefotri.. Two species were identified in each of the genera Absidia, Cladosporium, Emericella, Mucor and Paecilomyces. The rest genera that included Alternaria, Cunnighamella, Chaetomium, Corynascus, Eupenicillium, Fusarium, Gymnoascus, Melanocarpus, Monilia, Pestatiolopsis, Phaeoacremonium , Phialophora, Rhizopus, Sordaria, Stachybotrys, Scytalidium, Thermomyces, Trichoderma and Ulocladium were each represented by one species. The highest similarity index for fungal community inhabiting soil at both sites was found in soil at O1 layer (Atrush) and O2 layer (zawita).The least (SI) was recorded between O1 layer (Zawita) and O2 layer (Atrush). Absidia spinosa, and Mucor plumbeus are newly recorded from Iraq; hence they represent new additions to the Iraqi mycobiota.